Environmental violation fines growth in the northern region of Santa Catarina State, Brazil - Costa J.S.* (2020)
© 2020 Universidade Federal Rural do Rio de Janeiro (UFRRJ).This study aimed to diagnose the environmental infractions that occurred in the northern region of Santa Catarina State (Southern Brazil). The environmental infractions were classified by category and by violation activities concerning the hydrographic regions of Canoinhas Plateau and Baixada Norte from 2014 to 2018 to assess the growth and causes of a diagnosis regarding the environmental damages occurrences. Results indicated that the major illegal environmental practices registered in both region are related to environmental violations regarding the damage caused in native vegetation, and these damages are caused without authorization of the competent environmental authority. In addition, it was also important to note the activity of maintaining birds in captivity and of functioning of potentially pollutant activities or establishments that do not have a license of the competent regional environmental agencies. Therefore, efforts from the Environmental Policy should be directed to implement a forest monitoring system using remote sensing technology apart from starting a stronger cooperation with municipal authorities from Santa Catarina State by promoting Environmental Monitoring Programs (EMP).